Reliability and validity of the Stroke and Aphasia Quality of Life Scale-39 (SAQOL-39) for a Serbian population. (4th March 2022) - VukoviĆ, Mile; Sukur, Željana; VukoviĆ, Irena; Salis, Christos; Code, Chris
Abstract: Purpose : Aphasia has a negative impact on a person's quality of life (QOL). The Stroke Aphasia Quality of Life-39 scale (SAQOL-39) is a widely-used measure of health-related quality of life (HRQOL) developed for people with aphasia that has been translated into several languages. Its psychometric properties have been examined not only in English, but also in other languages. This study examined the reliability and validity of a translation and adaptation of the SAQOL-39 into Serbian in Serbian-speaking people with aphasia. Method : Using forward and backward translation, the SAQOL-39 was translated and adapted from English into Serbian and its psychometric properties were examined in 90 Serbian-speaking people with a broad range of times post-onset of aphasia. Internal consistency, test–retest reliability and other analyses were conducted. Result : Internal consistency and test–retest reliability of the Serbian version was high (Cronbach's α > 0.9; ICC ≥0.87), which is similar to versions of the scale in other languages. Conclusion : The Serbian translation and adaptation of the SAQOL-39 was shown to be a valid and reliable measure of QOL in people with aphasia with reliable psychometric properties and is suitable for the assessment of Serbian people with aphasia.